(untitled) (Philological Studies, 2019)
The goal of this article is to examine the ontological basis of game and playfulness, which has its origin in the very beginning of the human culture as expressed in mythical consciousness. It researches the cosmology of different myths from Eastern and Western provenience, especially the ‘covering’ themes, the symbolism of primordial waters, the night, the state of sleep; as a draft that suggests the experience of the world as a hide-and-seek game of covering and discovering.